Chiral Cyclopentadienyl Ligands Enable a Rhodium(III)-Catalyzed Enantioselective Access to Hydroxychromanes and Phthalides - Ye, Baihua; Cramer, Nicolai (Synlett, 2015)
The demand for efficient chiral cyclopentadienyl ligands (Cpx) has increased significantly in recent years, partly because Cp*Rh(III) species have been developed as powerful catalysts for directed C–H functionalization reactions. However, a lack of suitable Cpx ligands has hampered the development of the corresponding enantioselective processes. We report expansions of the libraries of two generations of Cpx ligands and their corresponding rhodium(I) complexes. The potential of the rhodium complexes as catalysts was evaluated in enantioselective C–H functionalizations involving cyclizations across tethered aldehydes. The mild reaction conditions permit the syntheses of hydroxychromanes and phthalides in good yields and high enantioselectivities.
Keywords: asymmetric catalysis; ligands; rhodium; cyclizations; heterocycles